Analysis of the Impact of Electric Charging Infrastructure Provision Rules on the Calculation of Fast and Ultrafast Charging Service Costs at Time Base and Energy Base Charging Stations - Yundi Haekal Azizi; Hakimul Batih (Ridwan Institute, 2023)
This study aims to analyze the impact of the issuance of MEMR Regulation Number 1 of 2023 concerning the Provision of Electric Charging Infrastructure for Battery-Based Electric Motor Vehicles, especially focusing on provisions related to electricity tariffs on surcharge fees for KBLBB fast charging and ultrafast charging consumers/customers. The calculation of surcharge fees can be economically affected by investment costs, operational costs, electric vehicle volume, and charging energy per electric vehicle (EV), so this study on surcharge fees is calculated using several scenarios and simulations carried out. The scenario is based on investment costs and operational costs using high and low cost financing calculations, and the simulation in question is on the volume of energy and electric vehicles over the next 15 years with pessimistic, moderate and optimistic simulations. This study uses quantitative descriptive methods that aim to describe or descriptive about a situation objectively using numbers, starting from data collection, interpretation through analysis of the data and appearance and results. The results of calculations from scenarios and simulations that have been carried out, calculations that are close to economics and based on current conditions that low cost scenarios with moderate simulations are appropriate recommendations to be applied at this time. Of course, the amount of application of the service fee must be evaluated by the Government every year, because the calculation component greatly affects the amount of the service fee.